ISLAM DAN DEMOKRASI - Muhammad Taufik; Ardillah Abu (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2020)
Democracy is a word that is very popular among the people, almost all levels of society know and understand the meaning of democracy well. Democracy is part of a political system and government which, according to Abraham Lincoln, is defined as government by the people, to the people and for the people. Democracy is one concept that comes from the West. Democracy was only included in the treasury of Islamic thought in the mid-19th century because it was considered to have good values ​​for life and not conflict with Islamic values. Therefore, they tried to find the equivalent of the word democracy in Islamic teachings, then the term shura was found. In the discourse and studies on the relationship between Islam and democracy, there are three opinions expressed by Islamic thinkers and figures about the relationship between Islam and democracy. First, there is no separation between Islam and democracy. Democracy is inherent or an integral part of Islam. Second, between Islam and democracy have conflicting relations. Third, in the relationship between Islam and democracy the third group does not accept it fully and does not reject it completely. This polemic of thought is then analyzed and studied further in accordance with the cultural context of Indonesian society.